A quantum-chemical study of phosphor impurity in BaTiO3 crystal - Stashans, A. (2007)
Structural and electronic effects produced by a P impurity in the cubic and tetragonal BaTiO3 lattices are investigated using a simple quantum chemical computer code based on the Hartree-Fock methodology. The obtained atomic displacements due to the defect present in otherwise pure crystal are mainly toward the impurity atom, thus reducing the interatomic distances within the defective region. It is also found that the phosphor produces some redistribution of electron density from the defect-neighboring atoms toward the chemical bonds thus diminishing the charges on atoms. We also observe a local energy level in the band-gap of material being composed mainly of P 3s atomic orbital. The level finds itself close to the top of the upper valence band, in no case contributing into the n-type conductivity in BaTiO3. © 2007 Wiley Periodicals, Inc.